Depression after Obstetric Fistula Repair - Stokes, Mary; Wilkinson, Jeffrey; Ganesh, Prakash; Nundwe, William; Pope, Rachel (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To measure depression using the PHQ-9 over time and to identify characteristics associated with persistent depression. Methods: A database of women undergoing obstetric fistula repair was used to examine association of depression with variables such as general demographics, type of obstetric fistula, surgical outcome, and continence status at the time of discharge. Results: 797 patients completed the PHQ-9 upon initial pre-operative assessment. 365 (45.8%) had a PHQ-9 score of 5 or higher, indicating symptoms of depression. Pre-operatively, depression was associated with the 18-34 year old age group and women with no children. Post-operatively, worse incontinence was associated with depression, however, over time depression was rarely found among women returning for follow-up. Conclusions: The decrease of depression seen over time is either due to selection bias or due to improved adjustment to one’s circumstances. Either way, this study underscores the need for ongoing follow-up, perhaps especially for those not presenting. Further studies are needed to assess the mental health of women who do not present for follow-up visits.